Ephrin-B2 Prevents N-Methyl-D-Aspartate Receptor Antibody Effects on Memory and Neuroplasticity - Planagumà, Jesús (Ann Neurol, 2016)
OBJECTIVE: To demonstrate that ephrin-B2 (the ligand of EphB2 receptor) antagonizes the pathogenic effects of patients’ N-methyl-D-aspartate receptor (NMDAR) antibodies on memory and synaptic plasticity. METHODS: One hundred twenty-two C57BL/6J mice infused with cerebrospinal fluid (CSF) from patients with anti-NMDAR encephalitis or controls, with or without ephrin-B2, were investigated. CSF was infused through ventricular catheters connected to subcutaneous osmotic pumps over 14 days. Memory, behavioral tasks, locomotor activity, presence of human antibodies specifically bound to hippocampal NMDAR, and antibody effects on the density of cell-surface and synaptic NMDAR and EphB2 were examined at different time points using reported techniques. Short- and long-term synaptic plasticity were determined in acute brain sections; the Schaffer collateral pathway was stimulated and the field excitatory postsynaptic potentials were recorded in the CA1 region of the hippocampus. RESULTS: Mice infused with patients’ CSF, but not control CSF, developed progressive memory deficit and depressive-like behavior along with deposits of NMDAR antibodies in the hippocampus. These findings were associated with a decrease of the density of cell-surface and synaptic NMDAR and EphB2, and marked impairment of long-term synaptic plasticity without altering short-term plasticity. Administration of ephrin-B2 prevented the pathogenic effects of the antibodies in all the investigated paradigms assessing memory, depressive-like behavior, density of cell-surface and synaptic NMDAR and EphB2, and long-term synaptic plasticity. INTERPRETATION: Administration of ephrin-B2 prevents the pathogenic effects of anti-NMDAR encephalitis antibodies on memory and behavior, levels of cell-surface NMDAR, and synaptic plasticity. These findings reveal a strategy beyond immunotherapy to antagonize patients’ antibody effects.